Heterogeneous dermatitis complaints after change in drinking water treatment: a case report - Bhatia Rajiv; Berger Magdalena; Weintraub June M (BMC, 2006)
Abstract Background The disinfectant monochloramine minimizes the formation of potentially hazardous and regulated byproducts, and many drinking water utilities are shifting to its use. Case presentation After a drinking water utility serving 2.4 million people switched to monochloramine for residual disinfection, a small number of residents complained of dermatitis reactions. We interviewed 17 people about their symptoms. Skin appearance, symptoms, and exposures were heterogeneous. Five respondents had history of hives or rash that preceded the switch to monochloramine. Conclusion The complaints described were heterogeneous, and many of the respondents had underlying or preexisting conditions that would offer plausible alternative explanations for their symptoms. We did not recommend further study of these complaints.